A Survey on the Best Choice for Modulus of Residue Code - reza omidi; ahmad towhidy; karim mohammadi (IAES Indonesian Section, 2019)
Nowadays, the development of technology and the growing need for dense and complex chips have led chip industries to increase their attention on the circuit testability. Also, using the electronic chips in certain industries, such as the space industry, makes the design of fault tolerant circuits a challenging issue. Coding is one of the most suitable methods for error detection and correction. The residue code, as one of the best choices for error detection aims, is wildly used in large arithmetic circuits such as multiplier and also finds a wide range of applications in processors and digital filters. The modulus value in this technique directly effect on the area overhead parameter. A large area overhead is one of the most important disadvantages especially for testing the small circuits. The purpose of this paper is to study and investigate the best choice for residue code check base that is used for simple and small circuits such as a simple ripple carry adder. The performances are evaluated by applying stuck-at-faults and transition-faults by simulators. The efficiency is defined based on fault coverage and normalized area overhead. The results show that the modulus 3 with 95% efficiency provided the best result. Residue code with this modulus for checking a ripple carry adder, in comparison with duplex circuit, 30% improves the efficiency.